Pemikiran dan Perjuangan Kiai Ahmad Ghazali Salim dalam Pembelajaran Bahasa Arab di Madura - Moh. Anwar (Tafhim Al-'Ilmi, 2018)
The purposes of this study are, first describing and analyzing the thought and effort of KH. Ahmad Ghazali Salimin Arabic learning in Madura. Second, describing and analyzing the methods used by KH.Ahmad Ghazali Salimin that Arabic learning in Madura. This study uses qualitative analysis research with exponent study approach,and the collection of data is conducted by interview, observation and documentation, all of which are used toanswer the problems of thought and effort of KH. Ahmad Ghazali Salim in Arabic learning in Madura.in this study,researcher found several findings of KH. Ghazali Ahmad Salim’s thought, effort and methode in Arabic learning.(1) The effort that conducted by KH. Ahmad Ghazali Salim in Arabic learning are; establishing the developmentbases of Arabic language in some islamic boarding schools, establishing his own islamic boarding school whichis specialized in the development of Arabic and islamic studies in Madura namedMa’had Darul -lughah Wa Al -Dirasat Al - Islamiyah, teaching Arabic language in various cottages and Universities in Madura. (2) KH. AhmadGazali Salim’s thought in Arabic language learning is, that his thought is original and accordance with the views ofmodern learning theories, especially behaviorism theory that emphasizes the external aspects of learners bycreating an arabic environment, giving stimulus and response to them, also kognitifisme learning theories thatemphasizes the internal aspects of the students that realized by providing subject matter intensively through thelearning process that involves an element of sense (cognitive) to digest and understand the subject matter. (3) Themethod applied by KH. A. Gazali Salim in Arabic learning includes four skills, namely; listening, speaking, readingand writing skills, that accordance with the Arabic popular learning methods that can be found in the book oflearning methods explained by the Arabic learning method experts.Key Word: KH. A. Gazali Salim, Thought, Struggle and Arabic Language AbstrakAdapun tujuan dari penelitian ini, Pertama, mendeskripsikan dan menganalisis pemikiran dan usaha KH. AhmadGazali Salim dalam pembelajaran Bahasa Arab di Madura. Kedua,mendeskripsikan dan menganalisis metodeyang digunakan oleh KH. Ahmad Gazali Salim dalam pembelajaran Bahasa Arab di Madura. Penelitian inimenggunakan penelitian analisis kualitatif dengan pendekatan studi tokoh, dan pengumpulan datanya dilakukandengan metode wawancara, observasi dan dokumentasi, yang semuanya digunakan untuk menjawabpermasalahn tentang pemikiran dan usaha KH. Ahmad Gazali Salim dalam pembelajaran Bahasa Arab diMadura.Dalam penelitian ini peneliti menemukan beberapa temuan tentang pemikiran, usaha dan metode KH.Ahmad Gazali Salim dalam pembelajaran Bahasa Arab. (1) Adapun usaha yang dilakukan beliau lakukan ;mendirikan markas pengembangan bahasa arab di beberapa pondok pesantren di Madura, Mendirikan pondokpesantren sendiri yang khusus dalam pengembangan Bahasa Arab dan Kajian–Kajian Ke-Islaman,mengajarBahasa Arab diberbagai Pondok-Pesantren dan Perguruan Tinggi di Madura. (2) Adapun Pemikiran KH.Ahmad Gazali Salim dalam pembelajaran Bahasa Arab adalah, bahwa pemikiran beliau merupakan pemikiranyang orisinil dan sesuai dengan pandangan teori-teori pembelajaran modern terutama teori pembelajaranbehaviourisme yang menekankan pada aspek eksternal pembelajar dan teori pembelajaran kognitifisme yangmenekankan pada aspek internal siswa (3) Adapun metode yang diterapkan KH. A. Gazali Salim dalam pembelajaranBahasa Arab sangat sesuai dengan metode-metode pembelajaran Bahasa Arab yang populer dan terdapatdalam buku-buku metode pembelajaran yang ditulis oleh para pakar metode pembelajaran Bahasa Aarab.Kata Kunci: KH. A. Gazali Salim, Pemikiran, Perjuangan dan Bahasa Arab